A positive working photoresist for i-line and a method for preparing the same

CN122902165APending Publication Date: 2026-10-13SUZHOU RUIHONG ELECTRONIC CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611271159.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

在实际生产中,现有光刻胶体系容易产生两类典型缺陷:一是表面不良(Mura),表现为涂布后膜厚不均、条痕或云雾状外观;二是针孔(Pin Hole),即光刻胶层中出现的微小孔洞

Benefits of technology

1、本申请通过采用硅氧烷改性酚醛树脂与含氟烷烃表面活性剂的协同组合,利用硅氧烷链段的低表面能特性与含氟表面活性剂的强界面吸附能力,在气-液及液-固界面形成混合吸附层,有效降低了光刻胶液在涂布过程中的动态表面张力,显著改善了大尺寸基板上的铺展均匀性与流平性,从而实现了无Mura、无针孔、无脱胶的高质量涂布效果。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to an I-line positive photoresist for a semiconductor and a preparation method thereof, and the preparation raw materials comprise the following components in parts by weight: modified phenolic resin 100 parts, diazonium naphthoquinone compound 15-25 parts, polyphenol additive 5-20 parts, organic solvent 300-600 parts, fluorine-containing alkane surfactant 0.01-1 part; the modified phenolic resin is a siloxane-modified phenolic resin. The I-line positive photoresist is simultaneously introduced with the siloxane-modified phenolic resin and the fluorine-containing alkane surfactant, so that the photoresist unexpectedly has the comprehensive performance that coating uniformity is obviously improved in a large-size panel coating process, Mura and pinhole defects are effectively eliminated, and delamination and abnormal morphology are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of photoresist technology, and in particular to a positive I-line photoresist for semiconductors and a method for preparing the same. Background Technology

[0002] In semiconductor and large-size panel manufacturing, photolithography is one of the core steps for pattern transfer. Among these, I-line (365 nm) positive photoresists are widely used in the manufacture of 2.5-generation and larger panels due to their high resolution and good process compatibility. A typical I-line positive photoresist mainly consists of alkaline-soluble linear phenolic resin, diazonaphthoquinone photosensitive compounds, and organic solvents; small amounts of functional additives may also be added when necessary.

[0003] However, with the increase in panel size and the diversification of coating processes (such as spin coating, blade coating, or a combination of both), higher requirements are placed on the coating performance of photoresists. In actual production, existing photoresist systems are prone to two typical defects: one is surface defects (mura), which manifest as uneven film thickness, streaks, or a cloudy appearance after coating; the other is pinholes, which are tiny holes appearing in the photoresist layer. These defects directly lead to a decrease in pattern transfer accuracy and contour distortion after development, severely reducing the yield of panel manufacturing.

[0004] Analysis revealed that the formation of mura and pin holes is closely related to the leveling properties of the photoresist on the substrate, the solvent evaporation rate, and the film uniformity. Traditional formulations often use low-boiling-point or single-type solvents. During high-speed coating and large-size substrate processing, excessively rapid solvent evaporation leads to a sharp increase in the viscosity of the resist, resulting in decreased local wettability and thus coating defects. Furthermore, existing photoresists lack a dedicated additive system for improving coating surface quality, making it difficult to simultaneously meet the requirements of high resolution and excellent coating uniformity.

[0005] To address the aforementioned issues, some improvement schemes have attempted to adjust the resin molecular weight or the structure of the photosensitive compound, but with limited success. Other schemes have introduced surfactants, but these often result in delamination or new morphological anomalies due to poor compatibility with other components. Therefore, developing a photoresist composition that can maintain high I-line resolution, significantly reduce Mura and Pin Hole, and adapt to various coating processes for large-size panels has become an urgent problem to be solved in this field. Summary of the Invention

[0006] To improve the coating uniformity and pattern transfer quality of I-line positive photoresist in large-size panel manufacturing, while obtaining excellent surface morphology and process compatibility, this application provides an I-line positive photoresist for semiconductors and its preparation method.

[0007] In a first aspect, this application provides a positive photoresist for semiconductors with an I-line, employing the following technical solution: A positive photoresist for semiconductor I-line, the raw materials for which are prepared include the following components in parts by weight: 100 parts modified phenolic resin, 15-25 parts diazonaphthoquinone compound, 5-20 parts polyphenol additive, 300-600 parts organic solvent, and 0.01-1 parts fluorinated alkane surfactant; wherein the modified phenolic resin is a phenolic resin modified with siloxane.

[0008] The inventors discovered that the use of siloxane-modified phenolic resin in combination with fluorinated alkane surfactants can produce a significant synergistic effect in I-line positive photoresist, which can effectively improve the uniformity of coating in large-size panels and suppress defects such as murmurs, pinholes, and delamination.

[0009] Analysis suggests this may be due to the following reasons: the flexible siloxane segments introduced into the siloxane-modified phenolic resin molecules have low surface energy, allowing them to spontaneously migrate to the gas-liquid or liquid-solid interface during adhesive coating, reducing the static surface tension of the system and thus improving the wettability of the adhesive on substrates such as glass and molybdenum. Meanwhile, the fluorinated alkane surfactant has extremely strong interfacial adsorption capacity, further reducing dynamic surface tension under dynamic coating conditions. The two types of low surface energy components do not undergo phase separation at the interface, but instead form a mixed adsorption layer through hydrophobic interactions, resulting in a better overall surface tension reduction effect than using either component alone. This facilitates rapid spreading and full leveling of the adhesive on large-size substrates, thereby eliminating Mura defects caused by surface tension gradients.

[0010] Meanwhile, the reduced surface tension improves the fluidity of the adhesive, allowing bubbles to escape more easily before the film cures, thus reducing pinhole formation. Furthermore, the siloxane segments and the non-polar portion of the fluorinated surfactant together construct flexible hydrophobic microdomains, which can moderately regulate solvent evaporation behavior (especially when combined with high-boiling-point solvents such as ethyl 2-hydroxypropionate), preventing stress concentration and cracking of the film layer due to excessively rapid solvent evaporation. During pre-baking curing, the siloxane segments form a micro-phase separation structure with the rigid framework of the phenolic resin. The siloxane-rich regions act as internal plasticizers, buffering curing shrinkage stress and reducing the risk of photoresist layer detachment from the substrate.

[0011] This application achieves a coating effect on large-size panels without Mura, pinholes, or delamination by synergistic combination of siloxane-modified phenolic resin and fluorinated alkane surfactant, within a wide range of organic solvent dosage and conventional coating process conditions. The quality of pattern transfer and process compatibility are significantly improved.

[0012] In one specific implementation, the modified phenolic resin is prepared by polycondensation reaction of phenolic compounds, aldehyde compounds and silicon-containing bisphenol monomers; the silicon-containing bisphenol monomer is 1,3-bis(4-hydroxybutyl)tetramethyldisiloxane, and its amount is 8-12% of the total weight of the phenolic compounds.

[0013] The inventors discovered that the modified phenolic resin prepared by co-condensation of the aforementioned silicon-containing bisphenol monomer with phenols and aldehydes exhibits superior interfacial properties and mechanical compatibility in photoresist systems compared to physically blended or unmodified resins. Analysis suggests this is primarily because, during the co-condensation process, siloxane segments are uniformly distributed in the resin molecular structure as side groups or chain segments, thus avoiding phase separation that may occur in physical blending.

[0014] Furthermore, when the amount of bisphenol monomer containing silicon is controlled within the range of 8-12% of the total weight of phenolic compounds, the surface energy reduction effect of the siloxane segments is balanced with the alkali solubility and film-forming properties of the resin itself: below 1%, the surface modification effect is not obvious; above 20%, it may excessively reduce the polarity of the resin, affecting the development performance and compatibility with photosensitive compounds. Within this dosage range, the siloxane segments can be stably enriched on the film surface and interface during coating and pre-baking processes, and at the same time form a synergistic adsorption layer with the subsequently added fluorinated alkane surfactants, thereby more effectively reducing dynamic surface tension, suppressing Mura and pinhole defects, and alleviating shrinkage stress through internal plasticizing during the curing stage, reducing the risk of degumming.

[0015] In one specific embodiment, the phenolic compound is selected from one or more of 2-methylphenol, 3-methylphenol, 4-methylphenol, 2,3-dimethylphenol, 2,4-dimethylphenol, 3,4-dimethylphenol, 2-ethylphenol, 3-ethylphenol, 4-ethylphenol, 2,3,4-trimethylphenol, 2,3,5-trimethylphenol, phenol, 2-hydroxyphenol, 3-hydroxyphenol, and 4-hydroxyphenol; the aldehyde compound is selected from formaldehyde, acetaldehyde, propionaldehyde, butyraldehyde, and 2-hydroxyphenol. One or more of the following: methylpropionaldehyde, pentanal, 2,2-dimethylpropionaldehyde, hexanal, heptanal, octanal, nonanal, decanal, acrolein, 2-butenal, propynal, glyoxal, malondialdehyde, succinal, benzaldehyde, 2-methylbenzaldehyde, 3-methylbenzaldehyde, 4-methylbenzaldehyde, 2,4-dimethylbenzaldehyde, 2,5-dimethylbenzaldehyde, 3,4-dimethylbenzaldehyde, 4-tert-butylbenzaldehyde, 4-ethylbenzaldehyde, 4-isopropylbenzaldehyde, 4-nonylbenzaldehyde, and 4-formylbenzaldehyde.

[0016] More preferably, the phenolic compound includes 3-methylphenol, 4-methylphenol and 2,4-dimethylphenol, wherein the weight ratio of 3-methylphenol, 4-methylphenol and 2,4-dimethylphenol is (3-7):(3-6):1; and the aldehyde compound is formaldehyde.

[0017] By employing the above technical solution, controlling the weight ratio of 3-methylphenol, 4-methylphenol, and 2,4-dimethylphenol within the range of (3-7):(3-6):1, a linear phenolic resin with suitable molecular weight distribution and moderate alkali solubility can be obtained. At this ratio, the substitution positions and density of methyl groups in the resin backbone can effectively regulate the activity of the phenolic hydroxyl groups, balancing the resin's solubility rate in alkaline developer with the inhibitory effect of photosensitive compounds, thus ensuring high resolution and good pattern contours under I-line exposure. Simultaneously, this composition provides ample reaction sites for subsequent siloxane copolymerization modification and exhibits good synergistic compatibility with fluorinated alkane surfactants and mixed solvents, which is beneficial for obtaining a uniform film layer free of murex and pinholes in large-size panel coatings.

[0018] If the ratio deviates from this range, for example, if the proportion of 3-methylphenol is too high or the proportion of 4-methylphenol is too low, the resin's alkali dissolution rate may be too fast, resulting in excessive etching of non-exposed areas during development and a decrease in resolution. Conversely, if the proportion of 2,4-dimethylphenol is too high, there will be too many dimethyl-substituted phenolic units in the resin, and the activity of the phenolic hydroxyl groups will be excessively masked, resulting in a slow alkali dissolution rate, which may cause development residue or reduced photosensitivity. In addition, an imbalance in the ratio can also affect the compatibility of the resin with diazonoquinone compounds, leading to poor film uniformity and even exacerbating Mura and pinhole defects. Therefore, limiting the weight ratio of the three phenols within the above range is crucial to balancing photolithography performance and coating quality.

[0019] In one specific embodiment, the diazonoquinone compound is prepared by esterification of diazonoquinone sulfonyl chloride with a polyphenol compound, with a degree of esterification of 1.2-3.8; the polyphenol compound is selected from one or more of 1,3-bis(2,4-dihydroxy-3,5-dimethylphenyl)benzene, 2,2'-methylenebis(4,6-dimethylphenol), tris(4-hydroxy-3,5-dimethylphenyl)methane, and 2-(3,5-dimethyl-4-hydroxybenzyl)-1,3,5-phenylpyrogallol.

[0020] By employing the above technical solution, the selected polyphenolic compound possesses a suitable number of phenolic hydroxyl groups and steric hindrance. After esterification with diazonaquinone sulfonyl chloride, the degree of esterification is controlled within the range of 1.2-3.8, forming a diazonaquinone compound that combines photosensitivity inhibition and alkali solubility adjustment capabilities. This type of compound rapidly undergoes photolysis under I-line exposure, generating indene carboxylic acid, transforming the exposed area into an alkali-soluble region and creating a good solubility contrast with the non-exposed area, thus ensuring high resolution and clear image contours. Simultaneously, the selected polyphenolic backbone (such as 1,3-bis(2,4-dihydroxy-3,5-dimethylphenyl)benzene or 2-(3,5-dimethyl-4-hydroxybenzyl)-1,3,5-phenylpyrogallol, etc.) exhibits good compatibility with siloxane-modified phenolic resins and fluorinated alkane surfactants, without affecting leveling and film uniformity during the coating process.

[0021] In one specific embodiment, the polyphenol additive is 2,6-bis(3,5-dimethyl-4-hydroxybenzyl)-4-methylphenol.

[0022] By adopting the above technical solution, 2,6-bis(3,5-dimethyl-4-hydroxybenzyl)-4-methylphenol, as a polyphenol additive, plays multiple synergistic roles in the photoresist system.

[0023] First, this polyphenol additive contains multiple phenolic hydroxyl groups, which can act as an alkali solubility rate regulator, moderately increasing the solubility rate of non-exposed areas in the developer. Simultaneously, it competitively absorbs I-line ultraviolet light with diazonaphthoquinone compounds, fine-tuning the photosensitive contrast and thus improving the steepness of image edges. More importantly, the multiple alkyl substituents (3,5-dimethyl) in its molecular structure endow it with certain hydrophobic properties, allowing it to weakly interact with the siloxane segments in the siloxane-modified phenolic resin and the hydrophobic portions of the fluorinated alkane surfactants during coating and drying, forming a local anchoring effect. This effect helps stabilize the mixed adsorption layer at the adhesive interface, preventing uneven film surface composition caused by excessive surfactant migration, thereby inhibiting the formation of mura.

[0024] Meanwhile, the polyphenol additive has a large volume and a rigid benzene ring skeleton, which can be embedded between the phenolic resin molecular chains during the pre-baking and curing process, appropriately increasing the free volume, thereby buffering the shrinkage stress difference between the siloxane chain segments and the rigid resin segments, and further reducing the risk of degumming.

[0025] Therefore, the polyphenol additive does not function independently, but rather forms a synergistic network with the siloxane-modified phenolic resin, the fluorinated alkane surfactant, and the diazonoquinone compound: the resin provides the framework and interfacial enrichment capacity, the surfactant is responsible for dynamically reducing surface tension, and the polyphenol additive plays a dual regulatory role in interfacial stabilization and stress buffering, thereby achieving defect-free coating of large-size panels within a wider process window.

[0026] In one specific embodiment, the organic solvent is selected from one or more of methyl 2-(2-butoxyethoxy)-2-methylpropionate, diethylene glycol monoethyl ether acetate, γ-butyrolactone, 2-methoxy-1-methylethyl acetate, 3-methoxybutyl acetate, ethyl acetate, methyl acetate, isopropyl acetate, isobutyl acetate, n-propyl acetate, 1-methoxy-2-propanol, and ethyl 2-hydroxypropionate.

[0027] More preferably, the organic solvent comprises 2-methoxy-1-methylethyl acetate and ethyl 2-hydroxypropionate, and the weight ratio of 2-methoxy-1-methylethyl acetate to ethyl 2-hydroxypropionate is (1-2):1.

[0028] By employing the above technical solution, 2-methoxy-1-methylethyl acetate and ethyl 2-hydroxypropionate are compounded at a weight ratio of (1-2):1 as an organic solvent system. Utilizing the difference in boiling points and the coordination of their evaporation rates, the leveling properties and film quality of the photoresist solution during coating can be optimized. 2-methoxy-1-methylethyl acetate, as the main solvent, has excellent solubility for multiple components such as phenolic resin and diazonoquinone compounds. Ethyl 2-hydroxypropionate, as a high-boiling-point auxiliary solvent, has a slower evaporation rate, which can moderately extend the leveling time window of the photoresist solution on the substrate, avoiding uneven film thickness and localized shrinkage stress concentration caused by rapid solvent evaporation. The synergistic effect of the two within the stated ratio range results in an ideal "slow-fast-slow" gradient in the overall evaporation curve of the solvent system, which helps eliminate Mura defects and suppress pinhole formation.

[0029] If the ratio deviates from this range, for example, if the proportion of 2-methoxy-1-methylethyl acetate is too high, the content of the high-boiling-point solvent ethyl 2-hydroxypropionate will be too low, resulting in excessively rapid overall solvent evaporation. The adhesive will solidify before spreading is complete, easily causing Mura defects such as surface streaks and cloud-like unevenness, while also increasing the pinhole rate. Conversely, if the proportion of ethyl 2-hydroxypropionate is too high, the overall solvent evaporation rate will be too slow, causing the adhesive to remain liquid for an extended period after coating. This may lead to uneven film thickness due to gravity or airflow disturbances, and prolongs the pre-baking process, affecting production efficiency. Therefore, limiting the ratio to within the range of (1-2):1 achieves a reasonable balance between ensuring coating quality and production efficiency.

[0030] In one specific implementation, the fluoroalkane surfactant is selected from one or more of perfluoroalkyl sulfonates, perfluoropolyethers, or perfluoroalkyl ethoxy ethers.

[0031] By employing the above technical solution, one or more of perfluoroalkyl sulfonates, perfluoropolyethers, or perfluoroalkyl ethoxy ethers are selected as fluorinated alkane surfactants. These surfactants possess extremely low critical micelle concentrations and strong interfacial adsorption capabilities, significantly reducing the dynamic surface tension of the adhesive solution at very low addition levels. Simultaneously, they form a hydrophobic-hydrophobic mixed adsorption layer with the siloxane segments in the siloxane-modified phenolic resin. The two layers synergistically align at both the gas-liquid and liquid-solid interfaces, further promoting rapid spreading and uniform leveling of the adhesive solution on large-size substrates, thereby effectively suppressing Mura and pinhole defects. Furthermore, these fluorinated surfactants exhibit good compatibility with polyphenol additives, diazonoquinone compounds, and mixed solvents, preventing phase separation or excessive migration during film formation and pre-baking processes, thus avoiding degumming or abnormal morphology.

[0032] Using non-fluorinated surfactants (such as ethers and siloxanes) has proven problematic, as demonstrated by testing: ether surfactants are prone to incompatibility with the system, leading to degumming, mura, or pinholes; siloxane surfactants may also exhibit mura and degumming. This indicates that only when the surfactant's fluorocarbon chain has sufficiently low surface energy and a suitable molecular structure can it form a stable multi-layered synergistic network with the siloxane-modified phenolic resin, polyphenol additives, and mixed solvents in this application, thereby ensuring good coating uniformity while avoiding defects. Therefore, limiting the fluorinated alkane surfactant to perfluoroalkyl sulfonates, perfluoropolyethers, or perfluoroalkyl ethoxy ethers is crucial to achieving the aforementioned synergistic effect.

[0033] Secondly, this application provides a method for preparing a positive photoresist for semiconductors using the I-line, employing the following technical solution: A method for preparing an I-line positive photoresist for semiconductors includes the following steps: The modified phenolic resin, diazonaphthoquinone compound, polyphenol additive, organic solvent and fluorinated alkane surfactant were mixed and shaken, and then filtered to obtain the I-line positive photoresist.

[0034] By employing the above technical solution, the I-line positive photoresist can be prepared simply by mixing, vibrating, and filtering modified phenolic resin, diazonium naphthoquinone compound, polyphenol additives, organic solvents, and fluorinated alkane surfactants in a specific ratio. This preparation method features simple process steps, mild operating conditions, and requires no complex equipment or special reaction conditions, making it suitable for industrial-scale mass production. Furthermore, the components are fully dispersed during mixing and vibration to form a uniform and stable photoresist system, avoiding poor component compatibility or defects introduced due to improper preparation processes. This ensures that the photoresist can stably exert its synergistic effect during subsequent coating, exposure, and development processes, thereby achieving a high-quality pattern transfer effect without mura, pinholes, or delamination.

[0035] In summary, this application includes at least one of the following beneficial technical effects: 1. This application utilizes the synergistic combination of siloxane-modified phenolic resin and fluorinated alkane surfactants. By leveraging the low surface energy of the siloxane segments and the strong interfacial adsorption capacity of the fluorinated surfactants, a mixed adsorption layer is formed at the gas-liquid and liquid-solid interfaces. This effectively reduces the dynamic surface tension of the photoresist solution during the coating process, significantly improves the spreading uniformity and leveling properties on large-size substrates, and thus achieves a high-quality coating effect without Mura, pinholes, or delamination.

[0036] 2. This application controls the amount of bisphenol monomer containing silicon within the range of 8-12% of the total molar amount of phenolic compounds, so that the siloxane segments are uniformly distributed in the modified phenolic resin main chain in the form of side groups or chain segments, thereby achieving a balance between the surface energy reduction effect and the resin's own alkali solubility and film-forming properties.

[0037] 3. This application utilizes a mixed solvent system of 2-methoxy-1-methylethyl acetate and ethyl 2-hydroxypropionate in a weight ratio of (1-2):1. By taking advantage of the difference in boiling points and the coordination of evaporation rates between the two, the solvent evaporation curve presents an ideal gradient of "slow-fast-slow". This ensures coating leveling and film uniformity while avoiding stress concentration due to film shrinkage. At the same time, the simple mixing and oscillation preparation process, with mild operating conditions and no need for complex equipment, is suitable for industrial mass production, ensuring that the photoresist can stably exert synergistic effects in practical applications. Detailed Implementation

[0038] The present application will be further described in detail below with reference to embodiments and comparative examples: Unless otherwise specified, all raw materials used in the examples and comparative examples are commercially available products.

[0039] Preparation Example 1 The formaldehyde used in this preparation example is specifically a 37% formaldehyde aqueous solution. The preparation of siloxane-modified phenolic resin is as follows: Five parts by weight of 3-methylphenol, four parts by weight of 4-methylphenol, one part by weight of 2,4-dimethylphenol, one part by weight of 1,3-bis(4-hydroxybutyl)tetramethyldisiloxane, 0.2 parts by weight of oxalic acid, and six parts by weight of formaldehyde were mixed and heated to 75°C for 1 hour, then heated to 90°C and reacted for another 4 hours. After the reaction was completed, the mixture was distilled under reduced pressure and dissolved and diluted with propylene glycol methyl ether acetate to control the solid content of the reaction resin solution at 50%. The solution was washed with water until the pH of the wash water reached 6.5, filtered, and dried to obtain siloxane-modified phenolic resin.

[0040] Preparation Example 2 The difference between Preparation Example 2 and Preparation Example 1 is that the phenolic resin obtained in Preparation Example 2 was not modified with siloxane, and its preparation is as follows: Five parts by weight of 3-methylphenol, four parts by weight of 4-methylphenol, one part by weight of 2,4-dimethylphenol, 0.2 parts by weight of oxalic acid, and six parts by weight of formaldehyde were mixed and heated to 75°C for 1 hour. The temperature was then increased to 90°C, and the reaction continued for another 4 hours. After the reaction was complete, the mixture was distilled under reduced pressure and dissolved and diluted with propylene glycol methyl ether acetate to maintain a solid content of 50%. The solution was washed with water until the pH of the wash water reached 6.5, filtered, and dried to obtain phenolic resin.

[0041] Preparation Example 3 The difference between Preparation Example 3 and Preparation Example 1 is that in the preparation step of the siloxane-modified phenolic resin obtained in Preparation Example 3, 1 part by weight of 1,3-bis(4-hydroxybutyl)tetramethyldisiloxane was replaced with 0.5 parts by weight of 1,3-bis(4-hydroxybutyl)tetramethyldisiloxane.

[0042] Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that in the preparation step of the siloxane-modified phenolic resin obtained in Preparation Example 4, 1 part by weight of 1,3-bis(4-hydroxybutyl)tetramethyldisiloxane is replaced with 1.5 parts by weight of 1,3-bis(4-hydroxybutyl)tetramethyldisiloxane.

[0043] Preparation Example 5 The diazononaphthoquinone sulfonyl chloride used in this preparation example is specifically 2,1,5-diazonaphthoquinone sulfonyl chloride; The preparation of diazonoquinone compounds is as follows: 1.9 parts by weight of 2-(3,5-dimethyl-4-hydroxybenzyl)-1,3,5-benzylpyrogallol were dispersed in 40 parts by weight of dioxane. At room temperature, 1.8 parts by weight of pyridine were added and mixed, followed by the dropwise addition of 5 parts by weight of 2,1,5-diazonaphthoquinone sulfonyl chloride. The mixture was stirred at room temperature for 3 hours. After the reaction was complete, the pH of the reaction solution was adjusted to 3.5 using dilute hydrochloric acid. The acidified reaction solution was then poured into a large amount of water, stirred to precipitate a solid, filtered, washed three times with water, and dried under vacuum at 50°C to obtain the didiazonaphthoquinone compound. Example Example 1

[0044] The preparation of the I-line positive photoresist is as follows: 100 parts by weight of the siloxane-modified phenolic resin prepared in Preparation Example 1, 20 parts by weight of the diazononaphthoquinone compound prepared in Preparation Example 5, 8 parts by weight of 2,6-bis(3,5-dimethyl-4-hydroxybenzyl)-4-methylphenol, 450 parts by weight of organic solvent (prepared by mixing 2-methoxy-1-methylethyl acetate and ethyl 2-hydroxypropionate in a weight ratio of 1.5:1) and 0.5 parts by weight of perfluoroalkyl ethoxymethyl ether were mixed and shaken at room temperature for 20 h. The mixture was then filtered using a filter with a pore size of 0.2 μm to obtain the I-line positive photoresist. Example 2

[0045] The only difference between Example 2 and Example 1 is that 100 parts by weight of the siloxane-modified phenolic resin prepared in Example 1 is replaced with 100 parts by weight of the siloxane-modified phenolic resin prepared in Example 3. Example 3

[0046] The only difference between Example 3 and Example 1 is that 100 parts by weight of the siloxane-modified phenolic resin prepared in Example 1 is replaced with 100 parts by weight of the siloxane-modified phenolic resin prepared in Example 4. Example 4

[0047] The only difference between Example 4 and Example 1 is that the 450 parts by weight of organic solvent (a mixture of 2-methoxy-1-methylethyl acetate and ethyl 2-hydroxypropionate in a weight ratio of 1.5:1) in the step of Example 4 is replaced with 450 parts by weight of organic solvent (a mixture of 2-methoxy-1-methylethyl acetate and ethyl 2-hydroxypropionate in a weight ratio of 0.5:1). Example 5

[0048] The difference between Example 5 and Example 1 is that the 450 parts by weight of organic solvent (a mixture of 2-methoxy-1-methylethyl acetate and ethyl 2-hydroxypropionate in a weight ratio of 1.5:1) in the step of Example 5 is replaced with 450 parts by weight of organic solvent (a mixture of 2-methoxy-1-methylethyl acetate and ethyl 2-hydroxypropionate in a weight ratio of 2.5:1). Example 6

[0049] The difference between Example 6 and Example 1 is that the 450 parts by weight of organic solvent (a mixture of 2-methoxy-1-methylethyl acetate and ethyl 2-hydroxypropionate in a weight ratio of 1.5:1) in the steps of Example 6 is replaced with 450 parts by weight of 2-methoxy-1-methylethyl acetate. Example 7

[0050] The only difference between Example 7 and Example 1 is that the 450 parts by weight of organic solvent (a mixture of 2-methoxy-1-methylethyl acetate and ethyl 2-hydroxypropionate in a weight ratio of 1.5:1) in the steps of Example 7 is replaced with 450 parts by weight of organic solvent ethyl 2-hydroxypropionate.

[0051] Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that 100 parts by weight of the siloxane-modified phenolic resin prepared in Preparation Example 1 is replaced with 100 parts by weight of the phenolic resin prepared in Preparation Example 2.

[0052] The positive photoresist prepared in each embodiment and comparative example was coated on a light glass sheet and a molybdenum-coated glass sheet. After scraping and spin coating, the excess solvent was evaporated by heating with a hot plate to obtain a uniform photoresist photosensitive layer sample. The prepared photoresist photosensitive layer sample is placed under a high-pressure mercury lamp and irradiated through a mask with a specific pattern; then it is developed using a 2.38% tetramethylammonium hydroxide aqueous solution, and after washing with water, the prepared pattern can be obtained.

[0053] The surface uniformity of the photoresist layer was tested using a film thickness gauge, and the integrity and flatness of the coated surface were evaluated using a high-resolution optical inspection system to confirm the absence of Mura (surface inhomogeneity) and pinhole defects. The coating quality was considered acceptable. The coating quality was quantitatively evaluated according to the grading standards in Table 1 below, and the test results are summarized in Table 2. Table 1. Evaluation Criteria for Coating Uniformity and Surface Defects of I-Line Positive Photoresist excellent ≤1% none none none good ≤3% Slight, does not affect the graphics ≤1 piece / cm² none qualified ≤5% Obviously, acceptable ≤5 pieces / cm² Slight edge Unqualified >5% serious >5 pieces / cm² obvious Table 2. Coating uniformity and surface defect performance data of the I-line positive photoresists prepared in each embodiment and comparative example. Example 1 ≤1% none none none excellent Example 2 ≤3% Slight, does not affect the graphics ≤1 piece / cm² none good Example 3 ≤3% Slight, does not affect the graphics ≤1 piece / cm² Slight edge good Example 4 ≤5% Obviously, acceptable ≤5 pieces / cm² Slight edge qualified Example 5 ≤3% Slight, does not affect the graphics ≤1 piece / cm² none good Example 6 ≤5% Obviously, acceptable ≤5 pieces / cm² Slight edge qualified Example 7 ≤3% Slight, does not affect the graphics ≤1 piece / cm² none good Comparative Example 1 >5% serious >5 pieces / cm² obvious Unqualified Furthermore, the photoresist photosensitive layer samples were tested for resolution, pattern contour, photosensitivity, and adhesion using the following test standards and procedures: 1. Testing steps for resolution and graphic outline: Exposure was performed using an I-line high-pressure mercury lamp (365nm) through masks with different linewidths / spacings, followed by development with a 2.38% TMAH aqueous solution. After washing, the minimum resolution linewidth was measured using CD-SEM, and the steepness of the pattern edges and development residue were observed.

[0054] 2. ISO sensitivity testing steps: Using a stepped mask or different energy gradients for exposure, the remaining film thickness after development at each energy is measured, dose-response curves are plotted, and the photosensitive threshold (E0, i.e., the energy at which the film thickness begins to change) is calculated.

[0055] 3. Adhesion test procedure: According to ASTM D3359, a grid (1mm×1mm, 10×10) is drawn on the photoresist film of the photoresist photosensitive layer sample. After being attached with special tape, the grid is peeled off and rated (0B-5B, 5B is the best).

[0056] The test results are summarized in Table 3: Table 3. Performance data of resolution, pattern profile, photosensitivity, and adhesion of the I-line positive photoresists prepared in each embodiment and comparative example. Example 1 ≤2 Steep (>85°) none ≤50 5B Example 2 ≤3 Steep (>85°) none ≤65 4B Example 3 ≤4 slight undercut slight ≤85 3B Example 4 ≤3 Tilt (70-85°) slight ≤70 4B Example 5 ≤3 Steep (>85°) none ≤65 4B Example 6 ≤3 Tilt (70-85°) slight ≤65 4B Example 7 ≤3 Steep (>85°) none ≤60 4B Comparative Example 1 >5 Undercut / Residue obvious >120 2B Based on Examples 1-7 and Tables 2 and 3, it can be seen that Example 1 achieves excellent performance in terms of coating uniformity, surface defect suppression, resolution, pattern contour, development residue, photosensitivity, and adhesion, exhibiting the best overall performance. Although Example 2 shows good coating uniformity, its resolution, photosensitivity, and adhesion are slightly inferior to Example 1, indicating that the surface modification effect is limited when the silicon content is below the preferred range. In Example 3, the silicon content exceeds the upper limit of the preferred range, resulting in decreased compatibility with the photosensitive compound, leading to development residue, decreased resolution, and reduced adhesion. In Example 4, excessive high-boiling-point solvent causes slow solvent evaporation, resulting in increased film thickness deviation and tilted pattern contour. Example 5 shows good overall performance. In Example 6, the lack of a high-boiling-point solvent to regulate the evaporation rate leads to increased surface defects. In Example 7, the use of a high-boiling-point solvent alone reduces resin solubility, affecting the uniformity of the adhesive solution. The above data indicate that when the silicon content is controlled within the preferred range and the proportion of high-boiling-point solvent in the mixed solvent is appropriate, the synergistic effect of each component is optimal.

[0057] Combining Example 1 and Comparative Example 1, and referring to Tables 2 and 3, it can be seen that Example 1 is significantly superior to Comparative Example 1 in terms of coating uniformity, surface defect suppression, resolution, pattern contour, development residue, photosensitivity, and adhesion. This indicates that there is a significant synergistic effect between the siloxane-modified phenolic resin and the fluorinated alkane surfactant: the siloxane segments spontaneously migrate to the interface during coating to reduce static surface tension, while the fluorinated surfactant further reduces dynamic surface tension. The two form a mixed adsorption layer at the interface, enabling the adhesive to spread and level rapidly on large-size substrates. At the same time, the siloxane segments act as internal plasticizers during the curing stage, buffering shrinkage stress, thereby effectively suppressing surface defects and improving resolution and adhesion.

[0058] This application achieves a significant improvement in the uniformity of positive photoresist coating and pattern transfer quality in the manufacturing of large-size panels by using a synergistic combination of siloxane-modified phenolic resin and fluorinated alkane surfactant, along with a mixed solvent of 2-methoxy-1-methylethyl acetate and ethyl 2-hydroxypropionate. This results in excellent surface morphology and process compatibility with no surface defects.

[0059] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A positive photoresist for semiconductors with an I-line, characterized in that, The raw materials for preparation include the following components in parts by weight: 100 parts modified phenolic resin, 15-25 parts diazonoquinone compound, 5-20 parts polyphenol additive, 300-600 parts organic solvent, and 0.01-1 parts fluorinated alkane surfactant; The modified phenolic resin is a phenolic resin modified with siloxane.

2. The positive photoresist for semiconductors according to claim 1, characterized in that, The modified phenolic resin is prepared by polycondensation reaction of phenolic compounds, aldehyde compounds and silicon-containing bisphenol monomers; the silicon-containing bisphenol monomer is 1,3-bis(4-hydroxybutyl)tetramethyldisiloxane, and its amount is 8-12% of the total weight of phenolic compounds.

3. The positive photoresist for semiconductors according to claim 2, characterized in that, The phenolic compounds are selected from one or more of 2-methylphenol, 3-methylphenol, 4-methylphenol, 2,3-dimethylphenol, 2,4-dimethylphenol, 3,4-dimethylphenol, 2-ethylphenol, 3-ethylphenol, 4-ethylphenol, 2,3,4-trimethylphenol, 2,3,5-trimethylphenol, phenol, 2-hydroxyphenol, 3-hydroxyphenol, and 4-hydroxyphenol; the aldehyde compounds are selected from formaldehyde, acetaldehyde, propionaldehyde, butyraldehyde, and 2-methylpropionaldehyde. One or more of the following: pentaldehyde, 2,2-dimethylpropionaldehyde, hexanal, heptanal, octanal, nonanal, decanal, acrolein, 2-butenal, propynal, glyoxal, malondialdehyde, succinal, benzaldehyde, 2-methylbenzaldehyde, 3-methylbenzaldehyde, 4-methylbenzaldehyde, 2,4-dimethylbenzaldehyde, 2,5-dimethylbenzaldehyde, 3,4-dimethylbenzaldehyde, 4-tert-butylbenzaldehyde, 4-ethylbenzaldehyde, 4-isopropylbenzaldehyde, 4-nonylbenzaldehyde, and 4-formylbenzaldehyde.

4. The positive photoresist for semiconductors according to claim 2, characterized in that, The phenolic compounds include 3-methylphenol, 4-methylphenol and 2,4-dimethylphenol, wherein the weight ratio of 3-methylphenol, 4-methylphenol and 2,4-dimethylphenol is (3-7):(3-6):1; the aldehyde compound is formaldehyde.

5. The positive photoresist for semiconductors according to claim 1, characterized in that, The diazononaphthoquinone compound is prepared by esterification of diazononaphthoquinone sulfonyl chloride with a polyphenol compound, with a degree of esterification of 1.2-3.8; the polyphenol compound is selected from one or more of 1,3-bis(2,4-dihydroxy-3,5-dimethylphenyl)benzene, 2,2'-methylenebis(4,6-dimethylphenol), tris(4-hydroxy-3,5-dimethylphenyl)methane, and 2-(3,5-dimethyl-4-hydroxybenzyl)-1,3,5-phenylpyrogallol.

6. The positive photoresist for semiconductors according to claim 1, characterized in that, The polyphenol additive is 2,6-bis(3,5-dimethyl-4-hydroxybenzyl)-4-methylphenol.

7. The positive photoresist for semiconductors according to claim 1, characterized in that, The organic solvent is selected from one or more of the following: methyl 2-(2-butoxyethoxy)-2-methylpropionate, diethylene glycol monoethyl ether acetate, γ-butyrolactone, 2-methoxy-1-methylethyl acetate, 3-methoxybutyl acetate, ethyl acetate, methyl acetate, isopropyl acetate, isobutyl acetate, n-propyl acetate, 1-methoxy-2-propanol, and ethyl 2-hydroxypropionate.

8. The positive photoresist for semiconductors according to claim 7, characterized in that, The organic solvent includes 2-methoxy-1-methylethyl acetate and ethyl 2-hydroxypropionate, and the weight ratio of 2-methoxy-1-methylethyl acetate to ethyl 2-hydroxypropionate is (1-2):

1.

9. The positive photoresist for semiconductors according to claim 1, characterized in that, The fluoroalkane surfactant is selected from one or more of perfluoroalkyl sulfonates, perfluoropolyethers, or perfluoroalkyl ethoxy ethers.

10. A method for preparing a positive I-line photoresist for semiconductors according to any one of claims 1-9, characterized in that, Includes the following steps: The modified phenolic resin, diazonaphthoquinone compound, polyphenol additive, organic solvent and fluorinated alkane surfactant were mixed and shaken, and then filtered to obtain the I-line positive photoresist.